Automated person tracking using proximity capacitive sensors - Arshad, Atika; Khan, Sheroz; Alam, A. H. M. Zahirul; Tasnim, Rumana (2014)
A proliferating concern has been growing on the development of non-contact sensing and monitoring of human activities in health care sectors to avert accidents of elderly patients. Keeping in mind the limitations of the existing techniques, a novel sensing technique for human movement recognition has been proposed in this paper which uses capacitive proximity sensors. This paper works towards setting the stepping stone of implementing capacitive sensor for a living style profile through MATLAB simulation. The output response for various capacitance values is plotted here proving its utility for precise measurement of voltage which is proportional to the electrical properties of patient's body at the sensing elements of the sensor. The output values measures the phase shift as a depiction of human movement. With the presence of a human body near sensor, signal waveform rises at a certain frequency peak and the movement of human body away from the sensor shows otherwise. The preliminary simulation result obtains accurate phase shift variations at a point frequency which is fruitful in further studies and reaching the ultimate goal of person's movement and activity tracking.